Interaction of Val66Met BDNF and 5-HTTLPR polymorphisms with prevalence of post-earthquake 27-F PTSD in Chilean population - Juan-Luis Castillo-Navarrete; Benjamin Vicente; Kristin Schmidt; Esteban Moraga-Escobar; Romina Rojas-Ponce; Paola Lagos; Ximena Macaya; Alejandra Guzman-Castillo (PeerJ, 2023)
Post-traumatic stress (PTSD) disorder is a mental health condition that can occur after experiencing or witnessing a traumatic event. The 27-F earthquake that struck Chile in 2010 was one such event that had a significant impact on the mental health of the population. A study was conducted to investigate the prevalence of PTSD and its associated factors among survivors of this earthquake. The study was a longitudinal design, involving a sample of 913 patients aged 18 to 75 years who attended 10 Primary Care Centers in Concepción, Chile. The Composite International Diagnostic Interview (CIDI) was used to assess both depressive episodes (DE) and PTSD before and after the earthquake. The study also involved genotyping studies using saliva samples from the participants, specifically focusing on the Val66Met and 5-HTTLPR polymorphisms. Statistical analysis was performed to examine the association between different variables and the presence of PTSD. These variables included demographic factors, family history of psychiatric disorders, DE, childhood maltreatment experiences, and critical traumatic events related to the earthquake. The results showed that the incidence of post-earthquake PTSD was 11.06%. No significant differences were found between the groups of participants who developed post-earthquake PTSD regarding the Val66Met or 5-HTTLPR polymorphisms. However, a significant association was found between the concomitant diagnosis of DE and the development of post-earthquake PTSD. The presence of DE doubled the risk of developing post-earthquake PTSD. The number of traumatic events experienced also had a statistically significant association with an increased risk of developing post-earthquake PTSD. The study’s limitations include the potential interference of different DE subtypes, the complexity of quantifying the degree of earthquake exposure experienced by each individual, and events entailing social disruption, such as looting, that can profoundly influence distress. In conclusion, the study found that PTSD following the 27-F earthquake in Chile was associated with a concomitant diagnosis of DE and the number of traumatic events experienced. The study did not find a significant association between PTSD and the Val66Met or 5-HTTLPR polymorphisms. The researchers recommend that mental health professionals should prioritize the detection and treatment of concomitant depressive episodes and exposure to critical traumatic events in survivors of disasters. They also suggest that further research is needed to better understand the relationship between genetic factors and post-disaster PTSD.